Regulatory B10 cells display an altered homoeostasis in acute graft‐versus‐host disease. (6th November 2016) - Chakupurakal, Geothy; Garcia‐Marquez, María Alejandra; Shimabukuro‐Vornhagen, Alexander; Kluth, Sandra; Schlosser, Hans; Theurich, Sebastian; Scheid, Christof; Hallek, Michael; Holtick, Udo; von Bergwelt‐Baildon, Michael
Abstract: Objective: The role of B cells and the subgroup of IL‐10 producing B cells, known to have a regulatory function, in patients following a haematopoietic stem cell transplant (alloSCT) has not been clearly understood to date. Methods: We prospectively recruited 95 patients following an alloSCT and studied the B‐cell reconstitution on days 30, 90 and 150. Regulatory B10 cells could be analysed in 22 consecutively recruited patients on day 30 post‐transplant. Results: The total B‐cell percentages in transplant recipients (median 0.33; range 0.01–5.9) were significantly reduced than the controls ( P = 0.0001) and constituted predominantly of transitional CD24 high CD38 high B cells. Regulatory B10 cells could be analysed in 22 consecutively recruited patients on day 30 post‐transplant. The percentages of B10 cells (median 1.35; 0.0–4.5) were significantly reduced in the transplant recipients in comparison with the control cohort ( P < 0.0001). Interestingly, the percentages of B10 cells in patients with acute GvHD (median 1.7; 0.33–4.5) were significantly higher than those without GvHD (median 0.7; 0–1.9) ( P = 0.0003). Conclusion: This is the first report demonstrating B10 cells in stem cell transplant recipients in the early post‐alloSCT (30 d) period. Our data suggest a possible role for B10 cells in the pathophysiology of acute GvHD. Further longitudinal studies are warranted to understand the implications of our findings.